Discovery of Morphostenophanes Pic, 1925 (Coleoptera: Tenebrionidae: Stenochiinae) in Xizang, China, with description of a new species - Zhou, De-Yao; Tenzin, Nyima; Zhang, Ren-Zhi (Zootaxa, 2026)
This study reports the first occurrence of the tenebrionid genus Morphostenophanes Pic, 1925 from Xizang, China, and describes a new species, M. medogensis Zhou & Zhang, sp. nov. Illustrations of the habitus and key diagnostic characters are provided to distinguish the new taxon from its congeners.